2008
DOI: 10.1002/term.66
|View full text |Cite
|
Sign up to set email alerts
|

The peritoneal cavity as a bioreactor for tissue engineering visceral organs: bladder, uterus and vas deferens

Abstract: Our objective was to produce avascular, myofibroblast-rich tissue capsules for use as autologous grafts for hollow, smooth muscle-walled visceral organs-bladder, uterus and vas deferens. To produce tissue for grafting, templates of the appropriate shape were implanted in the peritoneal cavities of rats or rabbits. After 2-3 weeks, the templates were removed, the encapsulating myofibroblast-rich tissue harvested and grafted to replace resected segments of bladder, vas deferens or uterus of the same animals in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…Up to 6 months after the surgery, no urethral stricture occurred. In previous studies, mesothelial cells have been shown to convert into urothelium when placed in the urinary tract [12,13,17]. We observed a similar phenomenon.…”
Section: Discussionsupporting
confidence: 78%
“…Up to 6 months after the surgery, no urethral stricture occurred. In previous studies, mesothelial cells have been shown to convert into urothelium when placed in the urinary tract [12,13,17]. We observed a similar phenomenon.…”
Section: Discussionsupporting
confidence: 78%
“…For example, when tubes of this myofibroblast-rich tissue (formed around a tubular molding im-planted into the peritoneal cavity for 2 to 3 weeks) are grafted into an autologous artery to replace excised segments, the tissue develops the characteristics of mature vascular smooth muscle and constituent cells express smooth muscle differentiation markers including smoothelin and the smooth muscle myosin isoform SM-2. 6,7 We present here a thorough cellular characterization of the myeloid cells involved in the inflammatory response to implanted foreign material. Specifically, we show that after the initial recruitment of monocytes and granulocytes, macrophages become the predominant cell within both the peritoneal cavity and the tissue capsule.…”
Section: Discussionmentioning
confidence: 99%
“…On harvest, the tissue has been used as an autologous graft for replacement/repair of hollow smooth muscle organs including blood vessels, bladder, vas deferens, and uterus. [5][6][7] Over the ensuing 2 to 3 months, the grafted tissue undergoes further cell differentiation and tissue remodeling to assume the morphology and function of the host organ. 8 In addition to providing a sterile location to develop myofibroblast-rich tissue for engineering purposes, the peritoneal cavity is a convenient site to investigate the involvement of myeloid cells in the inflammatory response.…”
mentioning
confidence: 99%
“…Attempts to create uterine patches date back to 2008, when Campbell et al 6 placed polyethylene bulbs into the peritoneal cavity and grew ''tissue capsules.'' These tissues were composed of myofibroblasts, which likely originated from host peritoneal fluid.…”
Section: Introductionmentioning
confidence: 99%